2004
DOI: 10.1029/2003ja010279
|View full text |Cite
|
Sign up to set email alerts
|

The Harris magnetic field: A laboratory realization of the topology based on energy resonance

Abstract: [1] An often-used approximation to the magnetotail field and the reconnection layer magnetic fields is the modified Harris field which consists of a neutral sheet magnetic field profile B x (z)x along with a superimposed normal field B zẑ . We have designed a configuration of current-carrying conductors and Helmholtz coil fields aimed at producing the topological characteristics of this field. In addition to mapping the geometry of the field we have appealed to another criterion of validity of this simulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…This bifurcation of trajectories was illustrated even in an earlier work by Speiser [1965] and quantitatively described in the paper by Büchner and Zelenyi [1989], that have shown that this phase difference Δ θ is a function of B z . A good deal of attention was devoted to so called CS resonances when Δ θ = π N and the next effect of chaotic scattering effectively is very small [ Chen , 1992; Walker et al , 2004].…”
Section: Quasiadiabatic Model Of Thin Current Sheetmentioning
confidence: 99%
“…This bifurcation of trajectories was illustrated even in an earlier work by Speiser [1965] and quantitatively described in the paper by Büchner and Zelenyi [1989], that have shown that this phase difference Δ θ is a function of B z . A good deal of attention was devoted to so called CS resonances when Δ θ = π N and the next effect of chaotic scattering effectively is very small [ Chen , 1992; Walker et al , 2004].…”
Section: Quasiadiabatic Model Of Thin Current Sheetmentioning
confidence: 99%